Burden of influenza disease in children under 2 years of age hospitalized between 2011 and 2020 in France. Issue 2 (February 2022) - Tillard, Célia; Chazard, Emmanuel; Faure, Karine; Bartolo, Stéphanie; Martinot, Alain; Dubos, François
Highlights: The burden of influenza in infants is less studied and appears to be underestimated. This study provides nationwide data on flu in infants for the period 2011–2020. 28, 507 children under the age of 2 were hospitalized with an influenza diagnosis. While mortality was low, morbidity of influenza in infants was high in France. Summary: Background: Although influenza viruses cause significant morbidity and mortality worldwide, the impact of these infections on children in France and in other European countries has not been extensively characterized. The primary objective of the present study was to describe the burden of influenza disease on hospitalized children under 2 years of age in France, using data from the national hospital discharge summary database (Programme de Médicalisation des Systèmes d'Information, PMSI). Methods: In a retrospective study of hospital admissions for influenza among children under the age of 2 in France, we extracted and analyzed hospital administrative data from the PMSI database (from January 1, 2011, to December 31, 2020). Results: From 2011 to 2020, 28, 507 children under the age of 2 were admitted to hospital with a primary or secondary diagnosis of influenza infection. The hospital admission rate was 205 per 100, 000 for children under the age of 2, 276 per 100, 000 for children under the age of 12 months, and 135 per 100, 000 for children aged between 12 and 23 months. Children under 6 months of age were the most affected (45.4%). An underlying condition was identified for 9.4% of the children, and 2.2% of the children were admitted to the intensive care unit. The death rate was 0.12 per 100, 000 for children under 2, 0.11 per 100, 000 for children under 12 months, and 0.16 per 100, 000 for children aged between 12 and 23 months. Conclusions: In France, the burden of influenza disease is significant in children under the age of 2.